Conceptual design of a semi autonomous mobile robot for pepper plantation - Alexander, Gotte (Universiti Malaysia Sarawak, UNIMAS, 2008)
Pepper is the king of spices and Sarawak in Malaysia is one of the largest producers in the world. In Sarawak, pepper vines are usually planted in secondary forest. The terrains of a pepper plantation can either be hilly or flat. Pepper berries are still manually harvested by human hands and there are no mechanical solutions at the moment. The purpose of conceptualizing the design of this mobile robot is to provide a more effective and fast method of harvesting pepper berries in the future. This mobile robot will be able to reduce the risk of human getting injured from harvesting the pepper berries. Axiomatic design approach is used to conceptualize this mobile robot. By using this approach the designer will be able to point out the limitation, function required and the design parameter by decomposing each function to multiple sub layers. This mobile robot implement two types of mechanism that is the active spoke system and the adjustable wheel support joint mechanism to overcome obstacles and avoid from being overturn on an uneven terrains. The conceptual mobile robot design is hypothesize to be able to adapt to the pepper plantation terrain.